2003
DOI: 10.1597/1545-1569(2003)040<0180:moiwpr>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Management of Infants With Pierre Robin Sequence

Abstract: Relieving airway obstruction by NPA is an effective and safe treatment for babies with PRS until they have grown out of their respiratory and feeding difficulties. It avoids the need for surgery and can be used on neonatal wards using the monitoring described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(46 citation statements)
references
References 23 publications
0
42
0
4
Order By: Relevance
“…Wagener et al reported successful outcomes in 20 children with PRS. In their study, the children required the airway for 16–104 days, and unfortunately this entire time was spent in hospital14 as processes to discharge children home with NPAs were not in place. Meyer et al in their study used NPAs in 29 of 38 children and found it successful in 48% 3…”
Section: Discussionmentioning
confidence: 99%
“…Wagener et al reported successful outcomes in 20 children with PRS. In their study, the children required the airway for 16–104 days, and unfortunately this entire time was spent in hospital14 as processes to discharge children home with NPAs were not in place. Meyer et al in their study used NPAs in 29 of 38 children and found it successful in 48% 3…”
Section: Discussionmentioning
confidence: 99%
“…70,71 Transitioning home with a stable NPA in place is possible when parents become comfortable with tube care and equipment. Discharge from the hospital with an NPA is now viewed as a safe and effective option for infants with RS in many institutions.…”
Section: Figurementioning
confidence: 99%
“…PRS often develops upper airway obstruction or feeding difficulty secondary to micrognathia, glossoptosis, or a shifted tongue that comes in contact with the pharyngeal wall [2]. Usually, progressive airway obstruction might become more noticeable in the second month of life.…”
Section: Introductionmentioning
confidence: 99%